“PENGARUH LATIHAN PEREGANGAN STATIS TERHADAP KELENTUKAN OTOT PUNGGUNG PADA PEMAIN BULUTANGKIS CLUB PERSATUAN BADMINTON ANGKASA PRESTASI GEMILANG PEKANBARU” - Rusmawanto Rusmawanto; Zainur Zainur; Ni Putu Nita Wijayanti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: The problem in this research is that the athlete's body position when doing the smash only makes jumps, in a stiff body position the knees are not bent so that the body movements are not harmonious. especially after assessing and warning whether there is an increase in muscle circumference. The format of this research is (using a one-group pre-post-test design approach) with the PB Angkasa Prestasi Gemilang team team population. The data in this research is a population of 12 people. The tool used in this research was the sit & reach test, which aims to determine the effect of static stretching exercises. Based on the analysis of the normality test on the independent variable (X), it produces a LoMax of 0.149 and an L table of 0.242, which means that LoMax <L table. The dependent variable (Y) returns a LoMax of 0.151 and an L table of 0.242. This means that LoMax <L The data table is normally distributed. In the hypothesis, the t-distribution can reject that the variable between x and the variable y is obtained by the value of t = 4,142, then tcount> ttable, namely (4,142)> (1,796), then Ha is accepted, in other words there is an effect of statistical stretching on muscle flexibility in badminton players. Badminton association Angkasa Prestasi Gemilang Pekanbaru.Key Words: Static Stretches, Flexibility Of The Back Muscles, Badminton